Radiotherapy for retroperitoneal liposarcoma: a report from the Transatlantic Retroperitoneal Sarcoma Working Group - Haas, Rick L. M.; Bonvalot, Sylvie; Miceli, Rosalba; Strauss, Dirk C.; Swallow, Carol J.; Hohenberger, Peter; Coevorden, Frits van; Rutkowski, Piotr; Callegaro, Dario; Hayes, Andrew J.; Honoré, Charles; Fairweather, Mark; et al. (Cancer, 2019)
Background The current study investigated the role of radiotherapy (RT) in patients with primary nonmetastatic retroperitoneal liposarcomas. Methods A total of 607 patients with localized retroperitoneal well-differentiated liposarcomas (WDLPS) and dedifferentiated liposarcomas (DDLPS) underwent surgical resection with or without RT at 8 high-volume sarcoma centers (234 patients with WDLPS, 242 patients with grade 1 to 2 DDLPS, and 131 patients with grade 3 DDLPS; grading was performed according to the National Federation of Centers for the Fight Against Cancer [Federation Nationale des Centres de Lutte Contre le Cancer; FNCLCC]). RT was administered in 19.7%, 34.7%, and 35.1%, respectively, of these 3 cohorts. Overall survival (OS) was estimated using the Kaplan-Meier method, and the incidences of local recurrence and distant metastasis (DM) were estimated in a competing risk framework. To account for bias consistent with nonrandom RT assignment, propensity scores were estimated. Cox univariable analysis of the association between RT and oncological endpoints was performed by applying inverse probability of treatment weighting (IPTW) using propensity scores. Results Age, tumor size, and the administration of chemotherapy were found to be significantly imbalanced between patients who did and did not undergo RT in all cohorts. IPTW largely removed imbalances in key prognostic variables. Although the 8-year local recurrence incidences in patients treated with surgery plus RT versus surgery only were 11.8% and 39.2%, respectively, for patients with WDLPS (P = .011;); 29.0% and 56.7%, respectively, for patients with grade 1 to 2 DDLPS (P = .008); and 29.8% and 43.7%, respectively, for patients with grade 3 DDLPS (P = .025), this significant benefit was lost after IPTW analyses. There were no significant differences noted with regard to DM and OS between irradiated and unirradiated patients across all 3 cohorts. Conclusions Perioperative RT was found to be associated with better local control in univariable unadjusted analysis in all 3 cohorts, but not after accounting for imbalances in prognostic variables. RT did not impact on DM or OS. The appropriate selection of RT in this disease remains challenging. The results of the European Organization for Research and Treatment of Cancer (EORTC)-Soft Tissue and Bone Sarcoma Group (STBSG) 62092-22092 prospective randomized trial are awaited.
Gesehen am 21.08.2019